International outbreak of monkeypox in men having sex with men - Soriano, Vicente; Corral, Octavio Jorge (AIDS Reviews, 2023)
On May 17, seven patients with monkeypox were reported in the United Kingdom (Mahase E. BMJ 2022). Since that time, more than 400 cases have been reported in 20 non-African countries, including Spain, Portugal, Italy, Sweden, USA, Canada, and Australia. Almost all are gay men under the age of 40. In Spain, the Ministry of Health has already confirmed 120 cases and there are another 50 suspects. Almost all have been diagnosed in Madrid.
Keywords: international outbreak; monkeypox; men; Scopus; JCR